Technological Literacy in Educational Programs in The Department of Accounting: As one of the Resources of Human Development (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Education is considered the corner stone of all nations development. It is the principal way for the development of human sources and the most achievements of the age due to the knowledge of these resources .                                              As its active role which accounting departments implement in Iraq universities , (public and private) through their teaching programs , they aim to supply labour-market with qualified cadre graduated as accountants auditors , tax auditors , financial analysts , academics …etc.These departments are considered the principal source of human development sources in Iraq .The essentiality of this research begins , at the present time , from its role that enables Iraq to achieve ever-lasting development kept pace with the development in the era of information technology and knowledge . Accounting developments face several challenges which require change in educational programs suit these development and be able to develop the capacities and skills of their out-comes , as qualified students or graduates to acquaint with work environment and to show the factors required to achieve that through "technology literacy" in accounting teaching programs for the graduates of accounting as a main source to develop this branch of study professionally and academically .The research resulted in a number of recommendation the most important one is that " Technology Literacy " should be included in accounting teaching programs through four-year study in the department of accounting as an objective to supply the students with the necessary skills and knowledge that enable them to apply these techniques in their practical lives , when they join the labour-market . Thus the universities should work on contracts with developed universities in the world to get experiences in this field and try to Shane such universities to develop the teaching programs in our universities.